Life table of Cochlochila bullita stål (hemiptera: tingidae) on Orthosiphon aristatus (blume) miq. and Ocimum basilicum l. in laboratory conditions - Tan, Li Peng; Sajap, Ahmad Said; Lee, Han Jeen; Lee, Seng Hua; Lum, Wei Chen (Universiti Putra Malaysia Press, 2015)
Ocimum tingid, Cochlochila bullita Stål (Hemiptera: Tingidae) is a pest of Lamiaceae plants such as basil, tulsi and coleus. It is now being recorded in Malaysia as a pest of the cat’s whiskers plant, Orthosiphon aristatus (Blume) Miq. Nevertheless, apart from its brief biological description, no other information is available. The life table of this pest was studied in laboratory conditions. Development time for C. bullita feeding on O. aristatus was 23.3 ± 0.9 days, which was found to be similar to those feeding on Ocimum basilicum (22.8 ± 0.3 days). Although C. bullita posts a higher mortality rate on O. aristatus than on O.basilicum (52% vs. 37%), the adult longevity of the bugs that feed on O. aristatus (♀: 33.9; ♂: 38.2 days) was found to be significantly higher than those bugs that feed on O.basilicum (♀: 27.2; ♂: 26.0 days). The pre-ovipostion, ovispostion and fecundity of C. bullita were also different between the host plants. The net reproductive rates (R0), finite rate of increase (λ) and intrinsic rate of increase (r) were also higher on O. aristatus (10.7504, 1.0690 and 0.0667), although there was an increased in immature survival on O. basilicum (6.0287, 1.0556 and 0.0541). Therefore, it is concluded that O. aristatus is as good as O. basilicum, or the population growth of C. bullita is more favoured as compared to O. basilicum.